2010
DOI: 10.1128/cmr.00043-09
|View full text |Cite
|
Sign up to set email alerts
|

The Era of Molecular and Other Non-Culture-Based Methods in Diagnosis of Sepsis

Abstract: SUMMARY Sepsis, a leading cause of morbidity and mortality throughout the world, is a clinical syndrome with signs and symptoms relating to an infectious event and the consequent important inflammatory response. From a clinical point of view, sepsis is a continuous process ranging from systemic inflammatory response syndrome (SIRS) to multiple-organ-dysfunction syndrome (MODS). Blood cultures are the current “gold standard” for diagnosis, and they are based on the detection of viable microorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
307
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(317 citation statements)
references
References 222 publications
(239 reference statements)
3
307
0
7
Order By: Relevance
“…2008; Mancini et al . 2010). Lastly, 16S rRNA gene sequencing can be less sensitive and slower than pathogen‐specific polymerase chain reaction (PCR) assays using panels of primers.…”
Section: Introductionmentioning
confidence: 99%
“…2008; Mancini et al . 2010). Lastly, 16S rRNA gene sequencing can be less sensitive and slower than pathogen‐specific polymerase chain reaction (PCR) assays using panels of primers.…”
Section: Introductionmentioning
confidence: 99%
“…Its most serious manifestation, septic shock, has a mortality of up to 70% [2]. There are conflicting reports in the literature concerning the outcomes of ICU patients with bacteraemia; for example, a Canadian study demonstrated that patients presenting to the ICU with bacteraemia did not have increased mortality compared to those without (OR 1.1 95% CI 0.7-1.8) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Blood cultures are the current gold-standard for detecting bacteraemia [2]. Collection of diagnostic information from blood cultures must be balanced with appropriate testing intervals and frequency to maximize the accuracy and usefulness of the procedure [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the microbiology laboratory, technological evolution is changing the identification process from conventional phenotypic techniques to PCR-and sequence-based methods. However, in contrast to viral diagnostics, culturebased methods are still dominating in clinical microbiology (Mancini et al, 2010). Over the past years, sequence analysis of the 16S rRNA gene has allowed identification of several new bacterial species or bacterial communities (Woo et al, 2008;Loncaric et al, 2011) and represents the "gold standard" for bacteria classification because of quality and accuracy of a sequence-based method and the availability of comprehensive databases such as the Ribosomal Database Project (RDP) (Cole et al, 2014) (Euzéby, 1997;Parte, 2014).…”
Section: Identification Of Microorganismsmentioning
confidence: 99%
“…For selected pathogens, specific PCR detection assays, including real-time PCR methods, have been developed: they are very powerful, simple, and effective tools for fast detection and identification, even directly from clinical or environmental specimens (Maheux et al, 2013). To bypass the main disadvantage of PCR-based identification technologies, that is, the one primer pair for each pathogen principle, diverse broad range and multiplex PCR protocols have been published to allow detection of the 35 main important pathogens in a single and closed-tube reaction format, considerably shortening the time to result and improving the outcome of patients (Dark et al, 2009;Mancini et al, 2010;Lucignano et al, 2011). In our laboratory, a high-resolution melting (HRM) PCR assay was developed for rapid and accurate differentiation of highly pathogenic Yersinia pestis strains from Yersinia pseudotuberculosis and highly pathogenic Bacillus anthracis strains from Bacillus cereus strains that allowed specific, rapid, and simple identification of these highly pathogenic bacterial species .…”
Section: Identification Of Microorganismsmentioning
confidence: 99%